Running training and co-ordination between breathing and running rhythms during aerobic and anaerobic conditions in humans - Bernasconi, P.; Burki, P.; Buhrer, A.; Koller, E. A.; Kohl, J. (European Journal of Applied Physiology, 1995)
The study was carried out on ten triathletes, six sprinters and ten subjects not trained in running (controls) to assess the effects of training history on the co-ordination between breathing and running rhythms during running on a treadmill. Three exercise intensities were used: 50%, 80% and 110% of the subject's anaerobic threshold (AT). All three intensities were performed twice: once with spontaneous breathing and once with breathing intentionally co-ordinated to the running rhythm. Heart rate, respiratory parameters and leg movements were continuously recorded. Blood lactate concentrations were measured discontinuously. The degree of co-ordination between running and breathing was quantified as the percentage of inspirations and/or expirations starting during the same phase of step. The results showed that the degree of both spontaneous and intended co-ordination at aerobic exercise intensities was in all three groups the same and increased in all groups with increasing intensity from 50% to 80% of AT; further increase of intensity to 110% of AT was associated with a significant decrease of co-ordination in controls and sprinters, whereas triathletes were able to maintain the same high degree of co-ordination as at 80% of AT. It was concluded that running training of either type at aerobic work loads had no effect on the co-ordination between running and breathing rhythms. At anaerobic intensities, however, the degree of co-ordination between running and breathing rhythms was higher in the endurance trained athletes than in the sprinters or in the untrained subjects. The degree of co-ordination increased with increasing regularity of breathing.